A compatible polymer acceptor enables efficient and stable organic solar cells as a solid additive. Issue 34 (17th August 2020) - Yang, Tao; Ma, Ruijie; Cheng, Hao; Xiao, Yiqun; Luo, Zhenghui; Chen, Yuzhong; Luo, Siwei; Liu, Tao; Lu, Xinhui; Yan, He
Abstract : Polymer acceptors with acceptor–donor–acceptor (A–D–A) building blocks have demonstrated great potential in achieving excellent power conversion efficiency (PCE) and stability in the field of organic solar cells (OSCs). Abstract : Polymer acceptors with acceptor–donor–acceptor (A–D–A) building blocks have demonstrated great potential in achieving excellent power conversion efficiency (PCE) and stability in the field of organic solar cells (OSCs). Currently, most of the A–D–A building blocks are composed of benzene-fused end groups, while other aromatic-fused terminal groups are rarely reported, which makes material diversity fall behind. Herein, a newly designed polymer acceptor with thiophene-fused end groups, namely PIDTC-T, is synthesized, which works well with PM6 in all-polymer OSCs based on their combination (PCE = 8.35%), indicative of its good compatibility with PM6. Critically, efficient liquid additive-free OSCs have been realized by doping PIDTC-T as involatile solid additive into the PM6:Y6 blend, achieving a remarkable PCE of 16.76% compared to the original 15.87%, along with better shelf life, photostability and thermostability. A similar achievement is obtained in as-cast PM6:Y6 devices. The mechanistic study reveals tuned morphology, complementary absorption spectra and adjusted composition distribution in devices, leading to higher mobility and suppressed recombination, which concurrently contribute to the improved photovoltaic performance of PM6:Y6 system. Our work can be considered meaningful as it helps in enriching material for polymer acceptors and fabricating stable and efficient OSCs without liquid additives.